Formulasi dan Aktivitas Antioksidan Krim Astaxanthin dengan Gelatin Kulit Ikan Patin (Pangasius hypophthalmus) sebagai Penstabil - Azlaini Yus Nasution; Ruwinda Ruwinda; Diana Nilawati (LPPM Universitas Abdurrab, 2024)
Astaxanthin has antioxidant activity, like other caratenoid compounds. Astaxanthin can protect cells or tissues from oxidative stress-induced damage. This research aims to formulate an astaxanthin cream preparation with the addition of catfish skin gelatin as a stabilizer and evaluate the characteristics of the cream preparation as well as testing the antioxidant activity of astaxanthin and the cream preparation using the DPPH method. Cream preparations are made with varying concentrations of 0; 0.05; 0.1 and 0.2% are named formulas F0, F1, F2, and F3 respectively. Evaluation of cream preparations includes organoleptic observations, homogeneity tests, pH tests, spreadability tests, and viscosity. The results of the organoleptic examination for each formula F0, F1, F2 and F3 are white, pink, red and brick red respectively, all formulas are odorless and are in semi-solid form. The homogeneity test showed that all preparations were homogeneous, the average pH range of the preparations was 6.40 ± 0.10 to 6.46 ± 0.05, the spreadability test was between 5.03 ± 0.05 to 5.16 ± 0.15 cm, viscosity 4984±177 to 6915±134. The evaluation results of the astaxanthin cream preparation have met the requirements. In testing the antioxidant activity of astaxanthin, the IC50 value was 3766.62 ppm, which was classified as inactive, and ascorbic acid as a comparison had an IC50 value of 6,799 ppm, which was classified as very strong. In the antioxidant test of the astaxanthin cream preparation, no antioxidant activity was detected and Garnier cream as a comparison produced an IC50 value of 19512334.96 ppm which was classified as inactive.